Cognitive Model types and the constructicon - Ibáñez (UNIRIOJA), Francisco Ruiz de Mendoza; Oyón (UNED), Alba Luzondo (ANTARES: Letras e Humanidades, 2018)
Construction Grammar approaches assume the existence of a constructicon, i.e. a network of grammatical constructions, or the conventionalized form-meaning pairings of a given language. However, construction grammarians generally offer analyses of constructions at one specific level of linguistic enquiry, without exploring the connections that exist with constructions belonging to other levels of description. The constructicon as a whole is thus hardly ever accounted for in a single explanatory theory or approach. Moving towards a more holistic view of language, this paper discusses the way in which a Construction Grammar model (the Lexical Constructional Model) deals with constructions of diverse nature and complexity and with parallel inferential meaning-making mechanisms by relating both to the common idealized cognitive model types that they exploit.